767 Are Full Length X-Ray Radiographs of The Femur Required in Neck of Femur Fractures with Co-Existing Malignancy?. (12th October 2021) - Ghobrial, M; Vaidya, A; Thahir, A; Krkovic, M
Abstract: Introduction: It is common practice that we obtain full-length femur x-ray radiographs in patients admitted with a neck of femur (NOF) and a history of co-existing malignancy. The aim of this retrospective study is to evaluate the type of malignancies associated with NOFs and whether obtaining a full-length femur X-rays changes the treatment plan. Method: Of the 2416 patients screened, 18% had co-existing malignancy (n = 431). The most common age to sustain a NOF with co-existing malignancy was 81, while 66% of them were females and 34% were males. The most common type of fracture sustained was an intra-capsular NOF (60%, n = 256), followed by inter-trochanteric fractures (31%, n = 133) and then sub-trochanteric fractures (9%, n = 42). Results: The one-year mortality was 29% (n = 125). One in four of these fractures were associated with a co-existing breast malignancy (25%, n = 107), followed by prostate cancer (13%, n = 55). Bladder, colorectal, skin SCC and lung cancer each contributed 6-7% (mean n = 29). Other cancers contributed to the rest of the 36%. Metastatic cancer to the skeletal system was noted in 7% of the patients(n = 30), resulting in a pathological fracture and 20% (n = 6) of these were contributed by a primary lung cancer. All in all, all of the 30 patients who had distant bone metastasis underwent the treatment they normally would undergo had the leg length femur X-rays not been done. Conclusions: In our series of patients with NOF fracture and existing skeletal metastatic deposits, the leg-length femur X-rays did not add any value related to the way the fractures were managed.